Shape and deformation of the Pampean flat slab in Argentina - Linkimer Abarca, Lepolt (2025)
The dominant forces shaping the unique geometries of flat slabs are still not fully understood. Knowing how the stress field changes with respect to the shape of the slab allows inferences of the dominant forces acting on the slab. In this study we calculated new models of the slab geometry and the intraslab stress field in the Pampean flat slab region of the Chile-Argentina Subduction Zone (latitude ∼25◦36◦S) where the Nazca Plate subducts together with the aseismic Juan Fernandez Ridge. To build the models, we used a catalogue of 1 059 well-located slab earthquakes recorded by the SIEMBRA and ESP temporary seismic arrays and calculated 411 new focal mechanisms that were analysed together with 407 focal mechanisms from other catalogues. Our results confirmed slab seismicity features such as a reverse dip (i.e. opposite to the subduction direction) of the seismicity band within the flat slab, two bands of descending seismicity and two regions with an absence of earthquakes. These seismicity patterns express the shape of the slab and its hydration state, with more localized slab dehydration along the inland path of the Juan Fernandez Ridge relative to the surroundings. In one of the regions without earthquakes, the slab is most likely continuous and dry, while in the other one the slab is missing, in agreement with previous works that proposed a hole in the slab visible with other methods. A comparison between the stress field and the local slab dip from both our new model and a previous one (Slab2) indicates that the dominant forces acting on the flat slab are the slab pull and the ridge buoyancy. Finally, the shape of the flat slab is controlled by the geologic migration of the Juan Fernandez Ridge, making the flat slab four times wider than the ridge offshore, and by the competing forces of the slab pull and the ridge buoyancy that creates a notable flexure (bulge) resembling the geometry of the outer rise near the trench.